ATRATIVIDADE E PREFERENCIA DE OVIPOSIÇÃO DE BEMISIA TABACI BIÓTIPO B (HEMIPTERA: ALEYRODIDAE) EM DIFERENTES CULTIVARES DE ALGODÃO. - Diniz, Jéssica; Toscano, Luciana Cláudia; Da Costa, Renato; Oliveira, Carlos Eduardo; Dos Santos, Renan Marcelo; Martins, Vinicius (ANAIS DO ENIC, 2018)
-